A review of the capability-based defence planning in Spain (2005-16) - Colom, Guillem (Papeles de Europa, 2017)
The article analyses the contemporary Spanish defense planning process from the enactment of the Ministerial Order 37/2005 that inaugurated the capability-based planning until the launch of the Ministerial Order 60/2015 that updates, flexibilizes and rationalizes the process. Its defining characteristics are described, its main virtues and limitations are reviewed and several ideas aimed at optimizing the planning cycles are proposed.